Dissection of Ire1 functions reveals stress response mechanisms uniquely evolved in Candida glabrata. - Taiga Miyazaki; Hironobu Nakayama; Yohsuke Nagayoshi; Hiroshi Kakeya; Shigeru Kohno (PLoS Pathogens, 2013)
Proper protein folding in the endoplasmic reticulum (ER) is vital in all eukaryotes. When misfolded proteins accumulate in the ER lumen, the transmembrane kinase/endoribonuclease Ire1 initiates splicing of HAC1 mRNA to generate the bZIP transcription factor Hac1, which subsequently activates its target genes to increase the protein-folding capacity of the ER. This cellular machinery, called the unfolded protein response (UPR), is believed to be an evolutionarily conserved mechanism in eukaryotes. In this study, we comprehensively characterized mutant phenotypes of IRE1 and other related genes in the human fungal pathogen Candida glabrata. Unexpectedly, Ire1 was required for the ER stress response independently of Hac1 in this fungus. C. glabrata Ire1 did not cleave mRNAs encoding Hac1 and other bZIP transcription factors identified in the C. glabrata genome. Microarray analysis revealed that the transcriptional response to ER stress is not mediated by Ire1, but instead is dependent largely on calcineurin signaling and partially on the Slt2 MAPK pathway. The loss of Ire1 alone did not confer increased antifungal susceptibility in C. glabrata contrary to UPR-defective mutants in other fungi. Taken together, our results suggest that the canonical Ire1-Hac1 UPR is not conserved in C. glabrata. It is known in metazoans that active Ire1 nonspecifically cleaves and degrades a subset of ER-localized mRNAs to reduce the ER load. Intriguingly, this cellular response could occur in an Ire1 nuclease-dependent fashion in C. glabrata. We also uncovered the attenuated virulence of the C. glabrata Δire1 mutant in a mouse model of disseminated candidiasis. This study has unveiled the unique evolution of ER stress response mechanisms in C. glabrata.